The European Welfare State between Transnational Migration and Exclusion - Seidl, Julian (Teisė, 2025)
The research paper explores the tensions between the EU’s principle of free movement and the restrictions on social benefits for EU citizens. While EU citizens can move and seek employment in another Member State, they might be excluded from social assistance benefits in the other Member State.The compatibility of these exclusions from social assistance benefits with the European law is questionable. Legal conflicts arise between the Regulation on the Coordination of Social Security Systems, which ensures equal treatment, and the Free Movement Directive, which allows exceptions during initial residency.In the 2010s, the European Court of Justice approved the exclusion of EU citizens from social assistance benefits in several decisions. However, a decision from 2021 begins to recognize a fundamental right to a minimum subsistence level, suggesting that the Member States must ensure that a refusal to grant social assistance does not expose Union citizens to an actual and current risk of violation of their fundamental rights.This paper argues that a fundamental rights guarantee of a minimum standard of living can be constructed on the basis of Article 1 and Article 34 Section 3 of the European Charter of Fundamental Rights.